Comparative Study for Virtual Personal Assistants (VPA) and State-of-the-Art Speech Recognition Technology - jaber, khalid; Lafi, Mohammed; Alkhatib, Ahmad AA; AbedAlghafer, Amani Khamis; Abdul Jawad, Mohammad; Ahmad, Amal Qassed (International Journal of Computational and Experimental Science and Engineering, 2024)
Numerous types of virtual assistants have emerged as a result of the widespread use of smartphones, the expansion of their services, the tremendous advancements in automatic speech recognition and AI, and the growing reliance on virtual personal assistants (VPAs) for basic daily tasks like playing music, sending texts, making restaurant reservations, and getting weather updates. The popularity of virtual personal assistants is largely attributable to their convenient blend of user-friendliness and natural language interaction. This study comprehensively examines various virtual personal assistants powered by AI. It briefly overviews each, such as Microsoft Cortana, Samsung Bixby, Apple SIRI, Google Assistant, and Amazon Alexa. This study also includes a comprehensive overview of the state-of-the-art speech recognition used in virtual personal assistants. The findings show that each Virtual Personal Assistant has advantages, and a user may select any of them depending on his preferences and needs.